Penggunaan Metode Bernyanyi dalam Meningkatkan Kemampuan Berbahasa Anak - Nurul Idhayani (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
The purpose of this study was to determine the increase in children's language skills through the use of the singing method in Group B children at Yapis Konda Kindergarten, Konda District, Konawe Selatan Regency. This research is a type of Classroom Action Research (CAR) which is carried out in 2 (two) learning cycles, each cycle consisting of 2 meetings with stages: planning, implementing, observing, evaluating and reflecting. The subjects of this study were group B students at Yapis Konda Kindergarten, Konda District, Konawe Selatan District, totaling 20 students consisting of 10 boys and 10 girls. The results of the research on the initial observation had classical completeness of 40%, namely only 8 students. in the first cycle there were 13 students (65%), then in the second cycle it increased to 18 students (90%) and exceeded the standard indicator of success that had been determined, namely 75%. These results indicate that the language skills of group B children in Kindergarten Yapis Konda, Konda District, South Konawe Regency can be improved through the use of the singing method.